Paul’s Account of Change at the Resurrection in 1 Corinthians 15:42-44a - Hollon, Elton L. (Heythrop journal, 2025)
The following article discusses Paul's conception of change regarding the resurrection body in 1 Cor 15:42-44a. Our thesis is that Paul uses a popular Hellenistic cosmology and account of change to explain how the transformation of the body is possible. He uses seed imagery to contrast the pre-and-post-resurrection bodies … the mortal and immortal bodies. Using rhetorical accommodation techniques, he resolves the Corinthian confusion regarding physical resurrection using popular Hellenistic ideas. Whereas some interpreters think that the resurrection body is terrestrial, others find a rarefied extraction of matter like the Stoic material soul or a holistic transformation into a rarefied and/or celestial element fitted to a polarized heavenly environment. Our interpretation is characterized by material continuity and integrative rather than absolute polarity. Though Paul conceives of material continuity, he says nothing of rarefied bodies or their natural habitat. Jesus's resurrection and anticipated return suggest a transformation of the ‘flesh’ into a body capable of traversing both heavenly-earthly spheres. Some think this view is incoherent, because it combines two incompatible conceptions of resurrection. Paul's solution seems to be that the resurrection body changes its properties as needed, depending on its environment. Hence, it never exemplifies incompatible properties at the same time.